Identification of novel bovine leukocyte antigen alleles and association of BoLA-DRB3.2*020:02:01 with resistance to Theileria orientalis infection in crossbred Kedah-Kelantan cattle: a pilot study - Agina, Onyinyechukwu Ada; Shaari, Mohd Rosly; Md Isa, Nur Mahiza; Ajat, Mokrish; Zamri Saad, Mohd; Hamzah, Hazilawati (Springer Science and Business Media B.V., 2024)
The bovine leukocyte antigen (BoLA) gene is a significant genetic part of the immune system and has been used as a disease marker in cattle. In this study, we detected Theileria orientalis, T. sinensis, Anaplasma marginale, Anaplasma platys, Candidatus Mycoplasma haemobos and Trypanosoma evansi by PCR amplification and sequencing of the amplicons. The allelic association of the BoLA-DRB3.2 gene with blood pathogen disease resistance and susceptibility in 87 Kedah-Kelantan x Brahman (KKB) and 38 Bali cattle was determined by Fisher’s exact test and Cochran Mantel Haenszel (CMH) correction test. Sequence-based typing of the BoLA-DRB3.2 gene identified 43 alleles (27 previously reported alleles and 16 novel alleles) across the two cattle breeds. Alignment analysis of the 16 novel alleles revealed 90.7–95.8% and 85–92% nucleotide and amino acid identities, with the reference allele, BoLA-DRB3*016:01 cDNA clone NR-1. BoLA-DRB3*009:02 (25.6%) and BoLA-DRB3*036:01 (36%) were the most frequent alleles in KKB and Bali cattle, respectively. In KKB cattle, BoLA-DRB3*020:02:01 was significantly associated with resistance to T. orientalis whereas *007:01 and *009:02 were significantly associated with resistance to C. Mycoplasma haemobos. Also, DRB3*017:01 was associated with susceptibility to T. orientalis in KKB cattle. In the Bali cattle, BoLA-DRB3*015:01 was found to be a genetic marker of susceptibility to C. Mycoplasma haemobos infection. Therefore, this study identified BoLA-DRB3.2 alleles associated with resistance and susceptibility to T. orientalis infection in KKB cattle and susceptibility to C. Mycoplasma haemobos infection in Bali cattle for the first time. Therefore, this study suggests that these BoLA-DRB3 resistance alleles could be used as candidate markers for selection, whereas susceptibility alleles could be used as candidate markers for culling in the beef industry.